Endotoxin-induced tumor necrosis factor alpha synthesis in murine embryo fibroblasts. - Havell, E A (1993)
Murine embryo fibroblasts (MEF) were found to secrete tumor necrosis factor (TNF) in response to stimulation with endotoxin. Endotoxin-induced TNF production by MEF was inhibited by cycloheximide. However, reversal of the effect of this inhibitor on protein synthesis results in TNF being secreted in amounts equivalent to those produced by endotoxin-induced MEF not treated with cycloheximide. Actinomycin D treatment of MEF blocked the production of endotoxin-induced TNF. Maximal production of TNF required MEF gene transcription during the first 6 h of incubation with endotoxin. To determine whether endotoxin-induced TNF alpha (TNF-alpha) and/or TNF beta were produced by MEF, cDNA was synthesized from the total RNA isolated from endotoxin-induced MEF and amplified by the polymerase chain reaction in the presence of oligonucleotide primers specific for each cytokine. On the basis of the polymerase chain reaction analysis, it was determined that TNF-alpha mRNA levels were increased in endotoxin-induced MEF. Thus, production of TNF-alpha by fibroblasts in response to the endotoxin component of bacterial cell walls is likely to contribute to the expression of TNF-mediated effects occurring in fibroblast-rich tissues infected with gram-negative bacteria.